Acute Pulmonary Compromise in a patient with Active Systemic Lupus Eritematosus: Case Report and literatura review - Farfán Chávez, Luis Gabriel (2025)
A 22-year-old male patient who went to the emergency room at Hospital III-1 José Cayetano Heredia in Piura due to acute respiratory symptoms, was hospitalized with Acute Respiratory Failure associated with a moderate Asthma Attack, Community Acquired Pneumonia and Systemic Lupus Erythematosus as a history. Throughout the hospital course, a complex interaction between asthma and the pulmonary manifestations of SLE is evident. For this reason, lupus pneumonitis was proposed as a diagnosis, with a good response to antibiotic treatment and pulse corticosteroids.